High-fidelity 3D live-cell nanoscopy through data-driven enhanced super-resolution radial fluctuation - Laine R.F.; Heil H.S.; Coelho S.; Nixon-Abell J.; Jimenez A.; Wiesner T.; Martínez D.; Galgani T.; Régnier L.; Stubb A.; Follain G.; Webster S.; et al. (Nature Research, 2025)
Live-cell super-resolution microscopy enables the imaging of biological structure dynamics below the diffraction limit. Here we present enhanced super-resolution radial fluctuations (eSRRF), substantially improving image fidelity and resolution compared to the original SRRF method. eSRRF incorporates automated parameter optimization based on the data itself, giving insight into the trade-off between resolution and fidelity. We demonstrate eSRRF across a range of imaging modalities and biological systems. Notably, we extend eSRRF to three dimensions by combining it with multifocus microscopy. This realizes live-cell volumetric super-resolution imaging with an acquisition speed of ~1 volume per second. eSRRF provides an accessible super-resolution approach, maximizing information extraction across varied experimental conditions while minimizing artifacts. Its optimal parameter prediction strategy is generalizable, moving toward unbiased and optimized analyses in super-resolution microscopy.